Exploring the Influence of Game-Based Learning and School Environment on Learning Achievement: Does the Mediation of Self-Intention Matter? - Atoulloh Atoulloh; Aries Fitriani; Rihab Wit Daryono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to explore the influence of game-based learning and the school environment on student learning achievement and the mediating role of self-intention in influencing game-based learning and the school environment. Method: The quantitative survey method involved 100 students of MA Ma'arif Al-Mukarrom, Kauman, and Ponorogo, using probability sampling techniques with proportionate stratified sampling techniques. Data was collected through a questionnaire with a Likert scale, and data analysis was carried out using relevant statistical techniques. Results: The research results show a positive but less significant influence on game-based learning and the school environment on student learning achievement; however, with self-intention mediating it, it has a positive and significant influence. The implications of this research include the importance of developing learning strategies to improve more effective and efficient education and a school environment that can support learning. Recommendations for research are the need to integrate elements of motivation and self-development in game-based learning design and develop meta-cognitive skills. The final one is creating a school environment to create an atmosphere of motivation and social support and facilitate learning experiences. Novelty: This research highlights the role of student enthusiasm in connecting learning through games, school atmosphere, and learning achievement. This adds insight into the interaction of these factors and underlines the importance of paying attention to students' enthusiasm for learning.